Freud, the reluctant philosopher - Tauber, Alfred I. (Princeton University Press, 2010)
Freud began university intending to study both medicine and philosophy. But he was ambivalent about philosophy, regarding it as metaphysical, too limited to the conscious mind, and ignorant of empirical knowledge. Yet his private correspondence and his writings on culture and history reveal that he never forsook his original philosophical ambitions. Indeed, while Freud remained firmly committed to positivist ideals, his thought was permeated with other aspects of German philosophy. Placed in dialogue with his intellectual contemporaries, Freud appears as a reluctant philosopher who failed to r.